The Cardiomyocyte in Cirrhosis: Pathogenic Mechanisms Underlying Cirrhotic Cardiomyopathy - Dae Gon Ryu; Fengxue Yu; Ki Tae Yoon; Hongqun Liu; Samuel S. Lee (Reviews in Cardiovascular Medicine)
Cirrhotic cardiomyopathy is defined as systolic and diastolic dysfunction in patients with cirrhosis, in the absence of any primary heart disease. These changes are mainly due to the malfunction or abnormalities of cardiomyocytes. Similar to non-cirrhotic heart failure, cardiomyocytes in cirrhotic cardiomyopathy demonstrate a variety of abnormalities: from the cell membrane to the cytosol and nucleus. At the cell membrane level, biophysical plasma membrane fluidity, and membrane-bound receptors such as the beta-adrenergic, muscarinic and cannabinoid receptors are abnormal either functionally or structurally. Other changes include ion channels such as L-type calcium channels, potassium channels, and sodium transporters. In the cytosol, calcium release and uptake processes are dysfunctional and the myofilaments such as myosin heavy chain and titin, are either functionally abnormal or have structural alterations. Like the fibrotic liver, the heart in cirrhosis also shows fibrotic changes such as a collagen isoform switch from more compliant collagen III to stiffer collagen I which also impacts diastolic function. Other abnormalities include the secondary messenger cyclic adenosine monophosphate, cyclic guanosine monophosphate, and their downstream effectors such as protein kinase A and G-proteins. Finally, other changes such as excessive apoptosis of cardiomyocytes also play a critical role in the pathogenesis of cirrhotic cardiomyopathy. The present review aims to summarize these changes and review their critical role in the pathogenesis of cirrhotic cardiomyopathy.